2019
DOI: 10.1186/s12903-019-0741-5
|View full text |Cite
|
Sign up to set email alerts
|

The antiplaque/anticariogenic efficacy of Salvadora persica (Miswak) mouthrinse in comparison to that of chlorhexidine: a systematic review and meta-analysis

Abstract: Background The plant Salvadora persica (miswak) has a long history of use in oral hygiene. Associations between the use of Salvadora persica and decreased oral bacteria numbers and plaque scores have been reported. This systematic review and meta-analysis assessed the ability of Salvadora persica mouthrinses to reduce plaque/cariogenic bacteria, in comparison to that of chlorhexidine and/or placebo rinses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
(49 reference statements)
1
36
0
1
Order By: Relevance
“…There are many studies into the effect of miswak extract and chlorhexidine as well as other mouthwash solutions on the incidence of VAP and oral hygiene in ICU patients. Some of these reports have obtained results compatible with the present study, while some others have suggested findings contradictory to our research (40)(41)(42). Moeintaghavi et al addressed in vitro antimicrobial activity of miswak extract, chlorhexidine, and persica mouth-wash against major oral pathogens, and the results indicated that chlorhexidine involves more effective antibacterial activity than persica mouthwash and miswak at all tested concentrations.…”
Section: Discussionsupporting
confidence: 63%
“…There are many studies into the effect of miswak extract and chlorhexidine as well as other mouthwash solutions on the incidence of VAP and oral hygiene in ICU patients. Some of these reports have obtained results compatible with the present study, while some others have suggested findings contradictory to our research (40)(41)(42). Moeintaghavi et al addressed in vitro antimicrobial activity of miswak extract, chlorhexidine, and persica mouth-wash against major oral pathogens, and the results indicated that chlorhexidine involves more effective antibacterial activity than persica mouthwash and miswak at all tested concentrations.…”
Section: Discussionsupporting
confidence: 63%
“…Tooth decay is an epidemic problem in the world. While chemical mouthwashes have their own side effects such as discolorations of tongue and tooth surfaces, altered taste perception, soft tissue irritations and burning sensation [21], herbal mouthwashes can be an appropriate substitute for them [22,23,24]. Results of this study proved that a mouthwash containing T. polium can effectively decrease S. mutans population in the mouth, and this effect can last for at least three weeks after using the mouthwash.…”
Section: Discussionmentioning
confidence: 68%
“…Tooth decay is an epidemic problem in the world. While the chemical mouthwashes have their own side effects, including discolorations of tongue and tooth surfaces, alteration in taste perception, soft tissue irritations and burning sensation [23], herbal mouthwashes seem to be an appropriate substitute [24][25][26]. Results of this study proved that a mouthwash containing T. polium can effectively decrease S. mutans population in the mouth, and this effect can last for at least three weeks after using the mouthwash.…”
Section: Discussionmentioning
confidence: 80%